Investigating the relationship between usefulness and ease of use of living streaming with purchase intentions - Xie, Qing; Bali Mahomed, Anuar Shah; Mohamed, Rosmah; Subramaniam, Anusuiya (Springer, 2022)
Purchase intentions are a strong source of increasing profits and sales. Due to increased social media trends and usage, live streaming has become a significant way to sell products online. This study aims to investigate the relationship between usefulness and ease of use of live streaming with purchase intentions. Additionally, this study considered two potential mediators as affective trust and cognitive trust between ease of use and usefulness of living stream and purchase intention in Chinese settings. Affective trust stood as a potential full mediator, and cognitive trust partially mediated the linkage. Additionally, a serially mediated linkage was also confirmed. The authors used PLS-SEM analysis to estimate the two-stage analysis based on conformality analysis and structural model assessment for effects. Findings from SEM analysis confirmed the positive predictive power of ease of use and usefulness toward purchase intentions in China. These findings are very useful for policymakers, sales managers, and marketing managers to improve sales and revenue. Additionally, marketing strategy makers can launch a successful sales campaign through the live stream. Scholars are encouraged to apply the current model in other cultural contexts for future research.